On the Efficiency Price of Capital in a Dual Economy - Manne, Alan S. (Quarterly Journal of Economics, 1974)
I. Introduction, 574. — II. Algebraic formulation, 577. — III. Dual variables — aggregate utility and gradualist maximands, 580. — IV. Dual variables — terminal capital and income distribution maximands, 584. — V. An illustrative example, 589. — VI. Some extensions, 595.